Thermophilic Bacteria Strictly Obey Szybalski's Transcription Direction Rule and Politely Purine-Load RNAs with Both Adenine and Guanine - Lao, Perry J.; Forsdyke, Donald R. (Genome Research, 2000)
When transcription is to the right of the promoter, the “top,” mRNA-synonymous strand of DNA tends to be purine-rich. When transcription is to the left of the promoter, the top, mRNA-template strand tends to be pyrimidine-rich. This transcription-direction rule suggests that there has been an evolutionary selection pressure for the purine-loading of RNAs. The politeness hypothesis states that purine-loading prevents distracting RNA–RNA interactions and excessive formation of double-stranded RNA, which might trigger various intracellular alarms. Because RNA–RNA interactions have a distinct entropy-driven component, the pressure for the evolution of purine-loading might be greater in organisms living at high temperatures. In support of this, we find that Chargaff differences (a measure of purine-loading) are greater in thermophiles than in nonthermophiles and extend to both purine bases. In thermophiles the pressure to purine-load affects codon choice, indicating that some features of their amino acid composition (e.g., high levels of glutamic acid) might reflect purine-loading pressure (i.e., constraints on mRNA) rather than direct constraints on protein structure and function.